Tinjauan Hukum Islam terhadap Pembulatan Harga Paket Cod (Cash On Delivery) oleh Kurir pada Aplikasi Lazada - Madinah, Dina; Murniati, Murniati; Heryanti, Linda (Al Barakat, 2024)
Online buying and selling is now almost done by everyone, especially those who live in urban areas. Cash On Delivery is one of the payment methods in online buying and selling through Lazada. Online stores will send goods via courier services. This is where rounding occurs when the package delivered by the courier arrives at the buyer, the courier sometimes rounds up on the grounds that there are no denominations. Consumers feel reluctant to the rounding done by the courier because consumers do not get the change they should have received. This study aims to determine how the practice of rounding COD package prices by couriers on the Lazada application. In addition, this study aims to analyze the Islamic legal review of the practice of rounding COD package prices by couriers on the Lazada application. The research method used in this study is a qualitative research method with a field research type. In addition, the data collection techniques used in this study are interviews and documentation. The results of this study found that first, the practice of rounding prices in online sales with the Cash On Delivery (COD) system on the Lazada application should not be done because the courier does not inform consumers in advance about the rounding of the COD package price, this violates the terms of sale and purchase, namely the agreed price must be clear in amount. In addition, it violates the principles of Islamic business ethics regarding honesty and setting prices with transparency. Second, there are differences in consumer attitudes towards the nominal amount of rounding. When the buyer feels willing, the contract is permitted because it has met the terms of sale and purchase, namely the element of willingness. Meanwhile, if the buyer does not feel willing, it means that the contract is invalid because the terms of sale and purchase regarding willingness or 'antaradin are not fulfilled between the two parties.